Historical Sources of Educational Research in China - Lyubov Кalashnyk; Can Zhang (Pedagogical Discourse, 2013)
This paper is devoted to educational research sources in pedagogy of China and PR China both in our country and abroad. The peculiarity of the Chinese chronology (lunar calendar, calendar based on astronomical events and ruling dynasties, etc.) does not allow to understand adequately the course of the historical and pedagogical process in the country without the appropriate preparatory data. The article also focuses on a particular form of historical and pedagogical dating of works – on hieroglyph appearance. the basic principles of modern Chinese source-studying tradition – the introduction of the «Sinocentrism» policy and relying on their own achievements and historical traditions only are pointed to as conclusions.